Learning From the Future of Auckland’s Arts and Culture Sector. Designing Experiential Futures to Help Cultural Managers Address Institutional Constraints. - Silver, Harry Frederick Langbein (Auckland University of Technology, 2022)
This research explored how a design-led approach to Futures research might help cultural managers address institutional constraints. Past literature acknowledges that institutional constraints are caused by the prevailing economic paradigm. Neoliberalism’s narrow economic focus excludes core values of arts and culture institutions. These can be effectively addressed by imagining new realities, an approach not common in contemporary institutional innovation. Discursive Design engages the intellect using artefacts. Experiential Futures (XF) is a Discursive Design approach to future thinking recognised for its ability to create and explore alternative futures in the present. In this research, the Ethnographic Experiential Futures (EXF) methodology was used to assess if a group of cultural managers’ experiences of the future of Auckland’s arts and culture sector might help them to imagine and instigate institutional transformation. The research project found the EXF process enabled the participants to step out of their current institutional paradigm, consider alternative possibilities and identify actions required to achieve the desirable ones. However, the process does not support enacting what are often radical and rebellious tasks required to make them a reality. The report recommends further research to harmonise the relationship between EXF and direct political action.